Comparison of Right Heart Structural and Functional Changes in Patient Undergoing Mitral Valve Replacement with or without Preservation of Subvalvular Apparatus in Patients with Rheumatic Valvular Disease - Mahmud, Sohel; Husain, Sabrina Sharmeen; Rahman, Md Mustafizur; Khaled, Md Fakhrul Islam; Osmani, DMMF; Ahmed, Chaudhury Meshkat (University Heart Journal, 2025)
Background: Excision of subvalvular apparatus (SVA) during mitral valve replacement (MVR) had its impact not only on left ventricular function, but also on regional and global right-ventricular function. This study was to investigate MVR with subvalvular apparatus preservation (SAP) have any effect on right heart regional or global function or not. Methods: A total of 50 rheumatic heart disease patients were enrolled who had underwent MVR, with (group- I) or without (group-II) preservation of SVA from January 2013 to June 2014. Preoperative, postoperative and 6 months follow up echocardiographic parameters of the right heart function were taken. Results: The mean age of the patients were 32±8 years. In both groups female number were predominant. There was significantly improved right atrial, right ventricular dimensions in both the groups at 6 months’ follow-up but it was more marked in group I. There was no change in right ventricular systolic function before and after surgery in group I patients, group II patients showed deterioration of right ventricular function after surgery. Conclusion: Deterioration of right ventricular systolic function in non-preserved group following MVR. University Heart Journal 2025; 21(1): 17-23